THE SEMANTIC CLASSIFICATION OF ANIMAL SYMBOLS IN UZBEK (Ustozlar uchun, 2026)
This article explores the semantic classification of animal symbols in the Uzbek language, focusing on the cultural, emotional, and metaphorical meanings attached to specific animals. The study identifies major semantic categories, including positivity, negativity, strength, wisdom, and peace, and illustrates how these symbolic meanings appear in proverbs, idioms, and common expressions. By analyzing the cultural context behind these symbols, the article provides insight into how Uzbek speakers conceptualize human traits and social behaviors through animals.